2004
DOI: 10.1111/j.1365-294x.2004.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonallopatric and parallel origin of local reproductive barriers between two snail ecotypes

Abstract: Theory suggests that speciation is possible without physical isolation of populations (hereafter, nonallopatric speciation), but recent nonallopatric models need the support of irrefutable empirical examples. We collected snails (Littorina saxatilis) from three areas on the NW coast of Spain to investigate the population genetic structure of two ecotypes. Earlier studies suggest that these ecotypes may represent incipient species: a large, thick-shelled 'RB' ecotype living among the barnacles in the upper inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 68 publications
8
133
0
Order By: Relevance
“…(1) The mutation responsible for the local adaptation could be due to parallel evolution in the strict sense; that is, independent mutations controlling the locally adapted traits could have arisen and been driven to fixation in different geographic locations (Rolan-Alvarez et al, 2004;Panova et al, 2006;Quesada et al, 2007;Galindo et al, 2009). (2) The ecotypes could initially have evolved allopatrically and the current sympatric or parapatric distribution could be the result of secondary contact and introgression (Wilding et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…(1) The mutation responsible for the local adaptation could be due to parallel evolution in the strict sense; that is, independent mutations controlling the locally adapted traits could have arisen and been driven to fixation in different geographic locations (Rolan-Alvarez et al, 2004;Panova et al, 2006;Quesada et al, 2007;Galindo et al, 2009). (2) The ecotypes could initially have evolved allopatrically and the current sympatric or parapatric distribution could be the result of secondary contact and introgression (Wilding et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Schilthuizen (2000) suggested that ecotones may be "speciation-prone" -that adaptation to habitat across a pronounced environmental gradient may lead to the evolution of assortative mating, and to parapatric speciation. We consider it premature to claim the Littorina saxatilis clines described here, or in Galicia (Rolán-Alvarez et al 2004) as examples of 'incipient' non-allopatric speciation for several reasons. Our data are consistent with models of introgression following secondary contact.…”
Section: Adaptation Environment and Gene Flow 22mentioning
confidence: 99%
“…On the coast of Galicia, Spain, L. saxatilis is described as being in a state of incipient speciation (Rolán-Alvarez et al 2004), which, it is argued, is proceeding independently on several shores -thus leading the authors to refer to parallel instances of sympatric speciation. In Galicia, the morphotypes look quite unlike H and M, or E and S. The upper shore form (RB, ridged and banded) (Johannesson et al 1993) is a relatively large animal with a sculptured shell, both features which assist in resisting crab predation (Johannesson and Tatarenkov 1997).…”
Section: Adaptation Environment and Gene Flow 22mentioning
confidence: 99%
“…Therefore, here we will use the cDNA-AFLP technique and qPCR to compare the expression profiles between two ecotypes of Littorina saxatilis involved in an incomplete sympatric ecological speciation process [43-45], in order to provide insights into the role of differential gene expression on ecological adaptation.…”
Section: Introductionmentioning
confidence: 99%